Development of a Low Cost and Portable Ventilator Prototype - Amdan, Nor Hidayah; Huong, Audrey (Evolution in Electrical and Electronic Engineering, 2021)
A ventilator is one of the most important pieces of equipment every hospital should have. In practice, a ventilator is a bedside machine that takes over the breathing process of a patient suffering from respiratory failure. A ventilator works by pushing breathable air into and out of a patient’s lung mechanically. This paper outlines the development of a portable ventilator prototype that is substantially less expensive and can be developed in the event of a ventilator scarcity during a pandemic or disaster. The Artificial Manual Breathing Unit (AMBU) bag is used in the development of this prototype for automatic assisted ventilation. This study found the developed system performed better than the manual method in delivery of breaths with high consistency of 18.6 ± 1.45 bpm. This system can also be run on batteries for more than four hours. This prototype costs not more than RM200 lower than those in the market. It is also energy-efficient and portable, making it a feasible alternative for mass casualties and resource-limited scenarios. The future of this work includes the addition of assistive control mode for a more reliable and effective breath delivery.